Carbamoylmannose enhances the tumor targeting ability of supramolecular nanoparticles formed through host–guest complexation of a pair of homopolymers. Issue 4 (9th January 2017) - Yao, Xikuang; Zhu, Qiwen; Li, Cheng; Yuan, Kangjun; Che, Rui; Zhang, Peng; Yang, Chenchen; Lu, Wei; Wu, Wei; Jiang, Xiqun
Abstract : Bleomycin monosaccharide-decorated platinum-incorporating supramolecular nanoparticles showed excellent tumor targeting and antitumor efficacy. Abstract : Conjugation of sugars to antitumor drugs can facilitate drug binding to tumor cells and the saccharide motifs of bleomycins (BLMs) play a crucial role in tumor-seeking. Here, we synthesized BLM monosaccharide, carbamoylmannose, and subsequently prepared carbamoylmannose decorated platinum-incorporating supramolecular nanoparticles formed through the host–guest complexation of poly( N -vinylpyrrolidone) and poly(aspartic acid). The targeting effects of carbamoylmannose decorated supramolecular nanoparticles in various cancer cells and tumor-bearing mice were investigated. It was found that the nanoparticles showed a specific in vitro and in vivo carbamoylmannose-mediated cellular uptake and drug delivery. The cellular uptake of the nanoparticles followed the receptor-mediated endocytosis mechanism in cancer cells but not in healthy cells. In a murine hepatic H22 tumor model, it was demonstrated that the carbamoylmannose moiety increased the plasma concentration, tumor targeting ability and tumor penetration of the nanoparticles, leading to high tumor accumulation and superior antitumor efficacy. This carbamoylmannose molecule may bring an opportunity to design and construct inexpensive but highly efficient drug and gene delivery systems in the future.